The Utilization of Historical Sources In History Learning: The Press During The Indonesian National Movement (1907-1912) - Permana, Rahayu; Noviyanti, Rani; Nurbaity, Nurbaity (PT Maju Malaqbi Makkarana, 2025)
The utilization of historical sources, particularly newspapers from Indonesia's National Awakening period (1907–1912), holds significant value in history education. Newspapers such as Medan Prijaji, Bintang Hindia, and Sinar Djawa played a pivotal role in fostering national awareness and advocating for independence during colonial rule. These sources serve not only as historical records but also as tools for understanding the development of nationalist ideologies, public mobilization, and the socio-political dynamics of the time. Incorporating these sources into history education allows students to critically analyze primary documents, evaluate the authenticity of historical narratives, and connect past events with contemporary issues. The process of applying historical methods—heuristics, source criticism, interpretation, and historiography—enhances students' analytical skills and deepens their appreciation for the nation's struggles. However, challenges such as limited access to archival materials and the lack of teacher training hinder the effective use of these resources. Digitalization of archives and professional development for educators are key solutions to overcoming these barriers. Overall, the integration of historical newspapers from the National Awakening period enriches history education by fostering critical thinking, connecting students with their heritage, and promoting a deeper understanding of Indonesia’s historical trajectory and its relevance to the present.